The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41467-021-22704-0
|View full text |Cite
|
Sign up to set email alerts
|

Universal scaling laws of keyhole stability and porosity in 3D printing of metals

Abstract: Metal three-dimensional (3D) printing includes a vast number of operation and material parameters with complex dependencies, which significantly complicates process optimization, materials development, and real-time monitoring and control. We leverage ultrahigh-speed synchrotron X-ray imaging and high-fidelity multiphysics modeling to identify simple yet universal scaling laws for keyhole stability and porosity in metal 3D printing. The laws apply broadly and remain accurate for different materials, processing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(52 citation statements)
references
References 40 publications
1
49
2
Order By: Relevance
“…Lastly, the velocity (V) was the only parameter that had a moderate impact on the keyhole width, with all other parameters having poor correlation. Furthermore, the addition of feature P∕ √ VD highlights strong positive dependency with depth, which agrees with the work conducted by Gan et al [25] where they found that keyhole depth scales linearly with P∕ √ VD. It should be noted that the size of the dataset only consists of 14 X-ray imaging experiments, so the trends we observed are indicative rather than definitive.…”
Section: Spearman's Correlationsupporting
confidence: 91%
See 1 more Smart Citation
“…Lastly, the velocity (V) was the only parameter that had a moderate impact on the keyhole width, with all other parameters having poor correlation. Furthermore, the addition of feature P∕ √ VD highlights strong positive dependency with depth, which agrees with the work conducted by Gan et al [25] where they found that keyhole depth scales linearly with P∕ √ VD. It should be noted that the size of the dataset only consists of 14 X-ray imaging experiments, so the trends we observed are indicative rather than definitive.…”
Section: Spearman's Correlationsupporting
confidence: 91%
“…When compared to previous work by Gan et al [25], the current study shows that depth is more strongly correlated with P/VD than with P∕ √ VD . One thing to note is that they used the absorbed power in the material which they were able to estimate using absorptivity simulations, rather than the raw laser power, which is what is used in this work.…”
Section: Discussion Of the Resultscontrasting
confidence: 59%
“…Cunningham et al 25 reported a nonlinear relationship between the FKW angle and the power density ( ), which changes with the laser scan velocity as well as powder materials. Gan et al 44 found that the tangent of FKW angle is approximately proportional to the “keyhole number ” ( ), which is a scaled version of the normalised enthalpy. Here, we find even stronger agreement between the FKW angle and the normalised enthalpy product (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Within the keyhole-melting regime, recent studies have reported a sharp transition between stable and unstable keyhole melting, typically defined by the onset of keyhole porosity 16 , 25 , 44 . From our data, we observed that the threshold for this transition can vary significantly between alloys.…”
Section: Resultsmentioning
confidence: 99%
“…Once the peak temperature is higher than the boiling point of the material, due to the multireflection of the laser beam between the walls of the depression, the keyhole depression deepens, resulting in rising absorbed power [84,85]. In this situation, the absorptivity (called absorptivity 1 in our benchmark), η, can be expressed as [86]:…”
Section: Atomic Volume Electron Affinitymentioning
confidence: 99%